2014
DOI: 10.1107/s1399004714022755
|View full text |Cite
|
Sign up to set email alerts
|

Structural implications of the C-terminal tail in the catalytic and stability properties of manganese peroxidases from ligninolytic fungi

Abstract: The variable C-terminal tail of manganese peroxidases, a group of enzymes involved in lignin degradation, is implicated in their catalytic and stability properties, as shown by new crystal structures, molecular-simulation and directed-mutagenesis data. Based on this structural–functional evaluation, short and long/extralong manganese peroxidase subfamilies have been accepted; the latter are characterized by exceptional stability, while it is shown for the first time that the former are able to oxidize other su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 40 publications
6
48
0
Order By: Relevance
“…As mentioned, lack of oxidation in MnP6 has been rationalized by the extra C-terminal residues, and ABTS oxidation in MnP4 has been attributed to the larger opening in the propionates 14 . The substrate migration, however, reveals the best minimum in MnP4 placed at the main heme channel ( Figure 1C, see also the supporting video), with a second minimum (~7 kcal/mol higher in energy) located at the propionate channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, lack of oxidation in MnP6 has been rationalized by the extra C-terminal residues, and ABTS oxidation in MnP4 has been attributed to the larger opening in the propionates 14 . The substrate migration, however, reveals the best minimum in MnP4 placed at the main heme channel ( Figure 1C, see also the supporting video), with a second minimum (~7 kcal/mol higher in energy) located at the propionate channel.…”
mentioning
confidence: 99%
“…The other one, known as the main heme channel, is located in the heme edge at the distal histidine side. At first sight, the main difference between MnP4 and MnP6 (with 46% sequence identity and 57% sequence similarity) is the C-terminal tail: 29 extra residues in MnP6 block the propionate channel ( Figure 1A), deletion of which introduces ABTS oxidation in this enzyme at the expense of thermostability decrease 14 .…”
mentioning
confidence: 99%
“…and to a major acidic stability, but also showed that only short MnPs have the capacity of oxidizing ABTS independently (in the absence of Mn 2+ ) [78]. Fernández-Fueyo et al using PELE [56] and electronic couplings calculations by the fragment charge difference (FCD) approach [80], provided computational information for the ABTS oxidation at the heme-propionate channel and the relation between the C-tail length and the MnPs catalytic properties.…”
Section: Manganese Peroxidasementioning
confidence: 99%
“…Also, the total energy during the molecular dynamics remained without major variations, confirming the stability of the system. The role of the C-terminal tail in the catalysis and stability of MnP from Ceriporiopsis subvermispora was studied through dynamic ligand diffusion and QM/MM techniques [78]. In a study of over 31 fungal genomes [79], 3 MnP subfamilies were defined depending on the length of the C-terminal tail: short, long and extralong MnPs.…”
Section: Manganese Peroxidasementioning
confidence: 99%
See 1 more Smart Citation